'Is it like one of those infectious kind of things?' The importance of educating young people about HPV and HPV vaccination at school. Issue 3 (4th May 2017) - Davies, Cristyn; Skinner, Susan Rachel; Stoney, Tanya; Marshall, Helen Siobhan; Collins, Joanne; Jones, Jane; Hutton, Heidi; Parrella, Adriana; Cooper, Spring; McGeechan, Kevin; Zimet, Gregory; ,
Abstract: The National Human Papillomavirus (HPV) Vaccination Program in Australia commenced in 2007 for girls and in 2013 for boys, using the quadrivalent HPV [4vHPV] vaccine. In Australia, students are primarily vaccinated en masse, on school grounds, after parental/guardian consent is obtained. Students most often receive little, or no, education at school about HPV or HPV vaccination prior to immunisation. There is also some uncertainty about where young people can and should obtain reliable information about the vaccine, outside of school. We conducted a cluster randomised controlled trial of a complex intervention in schools. This study aimed to improve: (1) student knowledge about HPV vaccination; (2) psycho-social outcomes and (3) vaccination uptake. In this paper, we briefly outline our educational intervention and discuss its implementation by educators including facilitators and barriers. We also discuss the study findings pertaining to student knowledge about HPV and HPV vaccination and their attitudes to vaccination across control and intervention schools. Study results showed students in intervention schools demonstrate greater knowledge and understanding of HPV and HPV vaccination. Greater knowledge and understanding of HPV and HPV vaccination appeared to promote positive attitudes towards vaccination and supported confidence with vaccination.